Analisis Pengaruh Realisasi Belanja Modal Daerah, Tingkat Partisipasi Angkatan Kerja, dan Angka Partisipasi Sekolah terhadap Tingkat Pengangguran Terbuka di Kabupaten/Kota Jawa Barat (2020-2024) - Ariq Muzaki; Saparuddin Saparuddin; Herlitah Herlitah (Indo Publishing, 2026)
This study aims to analyze the influence of regional capital expenditure, labor force participation rate (LFPR), and school enrollment rate (SER) on the open unemployment rate (OUR) in 27 districts/cities of West Java Province during 2020-2024. Unemployment remains a serious structural problem in Indonesia, particularly in West Java as the province with the largest population and labor force. This research employs a quantitative approach with panel data regression using the Fixed Effect Model. Data were obtained from the Central Bureau of Statistics and the Ministry of Finance across 135 observations. The results indicate that regional capital expenditure has a negative but not significant effect on OUR (p-value 0.9212). LFPR has a negative and significant effect on OUR (coefficient -0.321508; p-value 0.0000). SER has a negative and significant effect on OUR (coefficient -0.376762; p-value 0.0005). The R² of 0.809898 indicates that 80.99% of the variation in OUR is explained by the three independent variables. These findings provide important implications for local governments in formulating more effective fiscal policies and improving human resource quality through education to reduce unemployment.